Comparison of GPS TEC measurements with IRI TEC prediction at the equatorial latitude station, Chumphon, Thailand - P. Kenpankho; K. Watthanasangmechai; P. Supnithi; T. Tsugawa; T. Maruyama (My University, 2011)
We have analyzed the total electron content (TEC) derived from dual-frequency GPS receivers (GPS TEC) at the Chumpon station, Thailand, during the period 2004–2006. The diurnal, monthly, and seasonal variation in the measured TEC is compared with the TEC derived from the IRI-2007 model as well as the TEC obtained from the International GNSS service (IGS). To date, TEC data at equatorial latitudes are limited. The Chumphon station (10.72°N, 99.37°E) is located at the equatorial latitude and the dip latitude of 3°N. The TEC from the IRI-2007 model is based on the actual F2 plasma frequency (foF2) measurement. The results of our study show that the TEC derived from the IRI-2007 model agrees with the GPS TEC data mostly in the morning hours, but that it generally underestimates the GPS TEC. The maximum differences are about 15 TECU during the daytime and 5 TECU during the nighttime. The underestimation is more evident at daytime than at nighttime. The noon-bite out phenomena are clearly seen for the IRI-2007 TEC, but not on the IGS TEC and GPS TEC. The general underestimation of the IRI-2007 model can be explained from the exclusion of the plasmasphere, whereas the large difference during noon bite-outs is caused by the difference in the slab thickness in the ionosphere between the IRI-2007 model and the actual measurement. When compared with the TEC from the IGS model, the TEC measurements at Chumpon appear to be quite similar.
Keywords: Noon; Plasmasphere; International Reference Ionosphere; Ionosphere and magnetosphere dynamics